1999
DOI: 10.1592/phco.19.8.565.31521
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin: A Review of Published Experience in the Treatment of Bipolar Disorder and Other Psychiatric Conditions

Abstract: Successful therapy with valproate and carbamazepine in patients with psychiatric disorders led to investigation of other anticonvulsants for similar indications. Gabapentin is a relatively new anticonvulsant being investigated for potential use in the treatment of bipolar disorder (BD), anxiety disorders, behavioral dyscontrol, and substance use disorders. Its favorable side effect profile, absence of the need for therapeutic drug monitoring, and minimal drug interactions give gabapentin a potential role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…GBP has been recently investigated for potential use in the treatment of psychiatric disorders [3]. Uncontrolled trials reported that GBP may be an effective and well-tolerated treatment for behavioral and psychiatric symptoms in patients with dementia [4].…”
Section: Discussionmentioning
confidence: 99%
“…GBP has been recently investigated for potential use in the treatment of psychiatric disorders [3]. Uncontrolled trials reported that GBP may be an effective and well-tolerated treatment for behavioral and psychiatric symptoms in patients with dementia [4].…”
Section: Discussionmentioning
confidence: 99%
“…Various authors of medical reviews on this subject have concluded that gabapentin should not be recommended for treatment of bipolar disorder and that double-blind, randomized controlled trials are needed to confirm any true efficacy of the drug in management of this condition. [18][19][20][21] Real-life practice involves instances of refractory bipolar disorder that exhaust the current treatment options. The Texas Medication Algorithm Project (TMAP) lists lamotrigine or gabapentin only as salvage therapy.…”
Section: Gabapentin In the Treatment Of Bipolar Disordermentioning
confidence: 99%
“…Gabapentin has been reported to be effective as therapy for bipolar disorders (for review see [33]) and social phobia [34]. Gabapentin has recently been described to improve sleep [35], suggesting yet another potential therapeutic use for this versatile compound.…”
Section: Neurologic and Psychiatric Indicationsmentioning
confidence: 99%